2012
DOI: 10.1080/21507716.2011.638019
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Decision Making Identified by Parents of Children Receiving Pediatric Palliative Care

Abstract: Background Parental decision making is a critical component in the provision of palliative and end-of-life care, yet factors that parents perceive as influencing this process, when they are making decisions for their children, have not been well characterized. Methods As part of a mixed-methods cohort study, we interviewed 73 parents of 50 pediatric patients who were referred to the hospital’s pediatric palliative care service. The semistructured interviews focused on “decision making for your child”; the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 25 publications
(23 reference statements)
4
85
3
1
Order By: Relevance
“…Previous studies 11,18 of good-parent beliefs have been conducted with parents of children with terminal cancer using open-ended interview questions and with parents of children receiving palliative care using semistructured interview questions, 19 providing a grounding for the good-parent attributes used in the present study. A previous study 36 implemented this discrete-choice methodology to assess 43 parents of patients in a pediatric intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies 11,18 of good-parent beliefs have been conducted with parents of children with terminal cancer using open-ended interview questions and with parents of children receiving palliative care using semistructured interview questions, 19 providing a grounding for the good-parent attributes used in the present study. A previous study 36 implemented this discrete-choice methodology to assess 43 parents of patients in a pediatric intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…Such self-defined views may provide parents with orientation and goals for decision making while helping them grapple with feelings of personal accountability. 19 …”
mentioning
confidence: 99%
“…The themes expressed in focus groups led us to the moral distress and work-related moral stress literature, which has been almost exclusively studied within the context of nursing, medicine, and humanitarian work (Austin et al 2007; Corley 2002; Hamric, Borchers, and Epstein 2012; Nilsson et al 2011). Moral distress, first described by Jameton (1984), occurs “when one knows the right thing to do, but institutional constraints makes it nearly impossible to pursue the right course of action” (6).…”
Section: Front-line Researchersmentioning
confidence: 99%
“…Jameton’s (1984) construct of moral distress also included how the moral conflict created by recognition of institutional constraints resulted in frustration, anger, and anxiety. Subsequent research has demonstrated associations between moral distress and job burnout, emotional exhaustion, and job cynicism (Hamric and Blackhall 2007; Hamric et al 2012; Joseph and Deshpande 1997; Maslach 2003; Schluter et al 2008; Ulrich et al 2007; Webster and Baylis 2000). Drawing on later work emphasizing the psychological disequilibrium aspects of Jameton’s theory (Wilkinson 1988; Zuzelo 2007), Lutzen and colleagues (2010) developed the Work-Related Moral Distress Questionnaire, which includes items describing both work-related moral conflicts and psychological reactions of practicing nurses.…”
Section: Front-line Researchersmentioning
confidence: 99%
See 1 more Smart Citation